2015
DOI: 10.1002/aic.14885
|View full text |Cite
|
Sign up to set email alerts
|

High pressure measurements and molecular modeling of the water content of acid gas containing mixtures

Abstract: Water content of three carbon dioxide containing natural gas mixtures in equilibrium with an aqueous phase was measured using a dynamic saturation method. Measurements were performed up to high temperatures (477.6 K = 400 o F) and pressures (103.4 MPa = 15,000 psia). The perturbed chain form of the statistical associating fluid theory (PC-SAFT) was applied to predict water content of pure carbon dioxide (CO 2 ), hydrogen sulfide (H 2 S), nitrous oxide (N 2 O), nitrogen (N 2 ) and argon (Ar) systems. The theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…In molecular simulation, water is usually modeled as a Lennard-Jones (LJ) sphere ( m = 1) with a diameter that is close to 3 Å. In previous work, we showed that the LJ (dispersion) parameter for water could be fit independently of the polar and hydrogen bonding parameters to water content data in n -alkanes. , Simulation efforts performed in our group to develop a molecular based water model showed that an effective water Lennard-Jones energy (ε W / k ) of 220 K was required to match the experimental water solubility in TraPPE alkanes. As previously mentioned, Fouad et al modeled the phase behavior and hydrogen bonding distribution in 1-alcohol + n -alkane binary systems using a two-site alcohol model.…”
Section: Parameter Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In molecular simulation, water is usually modeled as a Lennard-Jones (LJ) sphere ( m = 1) with a diameter that is close to 3 Å. In previous work, we showed that the LJ (dispersion) parameter for water could be fit independently of the polar and hydrogen bonding parameters to water content data in n -alkanes. , Simulation efforts performed in our group to develop a molecular based water model showed that an effective water Lennard-Jones energy (ε W / k ) of 220 K was required to match the experimental water solubility in TraPPE alkanes. As previously mentioned, Fouad et al modeled the phase behavior and hydrogen bonding distribution in 1-alcohol + n -alkane binary systems using a two-site alcohol model.…”
Section: Parameter Optimizationmentioning
confidence: 99%
“…Given the centrality of hydrogen bonding in the structure and thermodynamics of pure water and pure alcohols, self-association and cross-association among water and alcohol molecules is expected to play an important role in determining the thermophysical properties of the binary alcohol–water system. Incorporating the physics of such association in the equation of state modeling of the mutual solubility of water–alkane and water–acid gas systems has thus received extensive attention both in our group as well as in other research groups. Typically, the equation of state development is anchored using different versions of the statistical associating fluid theory (SAFT) equation of state including early versions, , the perturbed chain version of SAFT (PC-SAFT), ,, the polar versions of SAFT, the simplified version of PC-SAFT, ,, the variable range version of SAFT (SAFT-VR), SAFT-γ, and cubic plus association (CPA). ,,,, …”
Section: Introductionmentioning
confidence: 99%
“…Equations of state have also been developed for the water/CO 2 mixture. Models rooted in statistical mechanics, such as statistical associating fluid theory (SAFT) and cubic plus association (CPA) equations of state, are better suited for description of this system than purely empirical models, because of its highly nonideal character. Although these equations of state show remarkable accuracy in calculation or prediction of phase equilibria for the water/CO 2 mixture, temperature- or pressure-dependent model parameters are required, and these parameters need to be obtained by fitting to mixture experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the accurate determination of the water content of acid gas containing mixtures is essential for better process design and operation. As shown in Figure 1 (adapted from [26]), the perturbed chain form of the SAFT equation of state (PC-SAFT) [10,11] accurately predicts the water content of natural gas mixtures across a wide range of temperatures and acid gas compositions. SAFT has also found success in the upstream of the oil and gas industry, such as modeling of asphaltene phase behavior at reservoir conditions.…”
Section: Applications Of Saftmentioning
confidence: 99%